(untitled) (Multidisciplinary Journal of Science and Technology, 2025)
Diabetes mellitus (DM) is one of the most common chronic diseases, posing a major challenge to health systems worldwide. Effective management of DM requires not only drug therapy but also a comprehensive approach that includes educational programs and support from health care providers. This study aims to evaluate the impact of nursing care on the clinical outcomes of patients with diabetes mellitus as well as their quality of life. The study included a sample of 200 patients diagnosed with type 2 diabetes mellitus treated at an endocrinology center. Patients were divided into two groups: one group received standard treatment, while the second group additionally had access to nursing care, which included regular counseling, self-management education, and psychological support. Study methods included analysis of glycated hemoglobin (HbA1c) levels, questionnaires to assess quality of life and treatment adherence. The main results showed that patients who received nursing care achieved a significant reduction in HbA1c levels (1.7% on average) compared to the control group. In addition, the level of treatment satisfaction in this group of patients was 85%, significantly higher than in the control group (60%). These findings emphasize the importance of nurses’ active participation in the treatment process, which contributes not only to improving clinical outcomes but also to improving patients’ quality of life. The findings of the study support the need to integrate nursing care into the standards of diabetes care to achieve optimal outcomes and improve the overall health of patients with diabetes mellitus.